Role of Foreign Reserves in Exchange Rate Stability and Inflation Control: A Comparative Study of Saudi Arabia, UAE, Qatar, Kuwait, and Bahrain for the Period 2011–2025 - Ahmed Masood Shaalan (Research Parks Publishers, 2026)
The research aims to study role reserves foreign in stability price Disbursement Control on Rates inflation in countries council cooperation Gulf region: Saudi Arabia, The UAE, Qatar, Kuwait, And Bahrain, during The period 2011–2025. Depends Search on methodology standard comparison, pool between Analysis Descriptive and decline Economic To explore relationship between reserves foreign And all from stability Currency Nationalism and control in Inflation. It indicates Results Primary to that reserves foreign Represents tool Effective To support price Disbursement and reduce fluctuations Economic But it They differ in Its impact between countries because of size The economy diversity sources Income, and efficiency administration Politics Cash. As well appears that countries The reserves The large and policies flexible I managed from Preservation on levels Low relatively from Inflation, comparison In countries smaller or The least diversity in The economy. Availability. the study framework analytically For comparison between Policies reserves in countries The Gulf, and it stands out importance Strengthening administration reserves foreign To confront traumas Economic Foreign Ministry and investigation stability economic long The duration varies across different countries in general, and specifically within the countries included in the research sample. This contributes to... This is amazing Results in presentation Recommendations practical For the makers decision around to improve effectiveness reserves As a tool Effective and efficient policies Cash and finance.